The Changes of India's Attitudes towards Myanmar from Confrontative to Cooperative - Sugiarto Pramono; Nackor Kimetene (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
This article aims to explain the shift of India's foreign policy towards Myanmar, from confrontation toward cooperation that occurred at the end of the cold war. The findings of this study is that the shift is driven by a series of factors both at domestic and international level. At the domestic level the interests of business collaboration with the authorities of being behind merapatnya India to Myanmar. While at the international level a number of situations make India to position of behave that way. The collapse of the Soviet Union; Indian trade with Indochina; and the influence of China and Pakistan in Myanmar make India to approach Myanmar. this study is very interesting because it has economic and political implications in the future of Asia. Keywords: non-state actors, cooperation, confrontation, foreign policy.